Preservation of Hadis in the Era of Industrial Revolution 4.0 (IR 4.0): Issues and Challenges: Pemeliharaan Hadis Dalam Era Revolusi Industri 4.0 (IR 4.0): Isu dan Cabaran - Zulkipli, Shahril Nizam; Anas, Norazmi; Suliaman, Ishak; Muhamad Ramlan, Anaztasia Natasha; Che Ahmat, Amin (EDUCATUM Journal of Social Sciences, 2021)
Modern-day technological advancements have led to a more systematic learning in applying knowledge of hadis by means of websites, software and apps. These digital platforms nevertheless may be compromised due to cybercrime attacks, ability constraints to transfer hadis text to digital visuals, dissemination of false hadis, distortion of hadis understanding and so on. Thus, this paper describes the issues and challenges pertaining preservation of hadis in the framework of its transmission and dissemination in the era of Industrial Revolution 4.0 (IR 4.0). Research is performed through content analysis of primary (hadis) and secondary sources (journal articles, books, etc.) to achieve the study’s objectives. Therefore, this conceptual paper has outlined ideas along with solutions to resolve matters concerning digital hadis, to further strengthen the continuation of measures taken in preserving authority of hadis within cyberspace. The findings of this study can be used as a guide for using digital hadis by taking precaution measures from promoting unauthorised hadis.